2014
DOI: 10.1007/s11695-014-1367-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medicaid Status on Weight Loss, Hospital Length of Stay, and 30-Day Readmission After Laparoscopic Roux-en-Y Gastric Bypass Surgery

Abstract: These data should be considered as states expand Medicaid and make decisions regarding treatment of severe obesity. Interventions to decrease hospital LOS and the 30-day readmission rate, particularly in Medicaid patients, should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Despite these baseline differences, four of the seven studies reported similar proportions of weight lost at follow‐up among Medicaid and commercially insured patients . Three studies reported less weight loss in Medicaid recipients.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite these baseline differences, four of the seven studies reported similar proportions of weight lost at follow‐up among Medicaid and commercially insured patients . Three studies reported less weight loss in Medicaid recipients.…”
Section: Resultsmentioning
confidence: 93%
“…All seven studies reporting on weight outcomes observed a substantial weight reduction in all insurance groups . The reported outcome variables included the percent of excess weight lost, difference in weight or BMI between time points, and weight loss classified as suboptimal (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…8 Likewise, Jensen-Otsu and colleagues performed a single institution retrospective review and found no difference in lengths of stay or anastomotic complications between Medicaid and non-Medicaid bariatric surgery patients. 9 Further, Alexander et al reported that although the Medicaid patients presented with more comorbidities, the proportion of patients who resolved their comorbidities was similar between Medicaid (75%) and Commercial (74.1%) groups. 15 …”
Section: Discussionmentioning
confidence: 96%
“…6,7 Studies of patients with severe obesity have shown that Medicaid and non-Medicaid patients who undergo bariatric surgery have similar surgical outcomes such as lengths of stay and anastomotic complications. 8,9 Although differences in bariatric surgery costs between Medicaid patients and non-Medicaid patients have not been studied, findings in other specialties have varied.For example, Medicaid patients undergoing coronary artery bypass grafting had higher costs and longer lengths of stay, 10 while Medicaid patients undergoing spinal cord surgery generated lower costs compared to non-Medicaid patients. 11 …”
Section: Introductionmentioning
confidence: 99%
“…With regard to patient demographics and comorbidities, there were no single factors that were universally recognized among the literature as predictors for readmission. Among the most common patient demographics associated with 30-day readmission were medicaid status [20,21,28] and black race [19,23], but these factors are much less relevant in the Canadian setting. The only comorbidity that was identified in more than a single study was previous DVT [19,23].…”
Section: Discussionmentioning
confidence: 99%